A Modified Technique of Simple Suprapubic Prostatectomy: No Bladder Drainage and No Bladder Neck or Hemostatic Sutures - Moslemi, Mohammad Kazem; Abedin Zadeh, Mehdi (Urology Journal, 2010)
Introduction: Open prostatectomy is the conventional surgical treatment of benign prostatic hyperplasia. The major early complication of this procedure is bleeding. We introduce a technique of prostatectomy in order to prevent significant bleeding, reduce morbidity, and shorten convalescence and hospital stay periods. Materials and Methods: We enrolled 202 consecutive patients diagnosed with benign prostatic hyperplasia who were candidates for open prostatectomy. The operation was performed by one surgeon within 6 years using a modified technique of simple suprapubic prostatectomy (no bladder drainage and no bladder neck suture). Clot retention episodes, hemoglobin decrease, urethral catheterization time, and hospital stay were evaluated postoperatively. The patients were followed up for 1 to 2 years. Results: The mean operative time was 18 minutes (range, 14 to28 minutes) with an estimated mean intra-operative blood loss of 120 mL. The mean hospital stay was 3 days (range, 2 to 4 days). The median urethral catheterization time was 5 days. No intra-operative complication or mortality was noted. Return to baseline urinary function and subjective continence at 3 months were 100% and 99%, respectively. Only in 1 patient (0.4%), bladder neck contracture was detected 3 months after the operation. Conclusion: Transurethral prostate resection has been introduced as the surgical treatment of choice in patients with benign prostatic hyperplasia. However, open prostatectomy still has a place. Suprapubic prostatectomy with no bladder drainage and no bladder neck suture appeared to be successful in decreasing convalescence and hospitalization times, with no significant complication, major blood loss, or bladder neck contracture.